MXenes-based composite conductive aerogel and its preparation method and application

By combining carbon nanotubes with polyacrylonitrile fibers and crosslinking with MXenes material, a high-conductivity and compressibility MXenes matrix composite conductive aerogel was prepared, which solved the mechanical strength and conductivity of MXenes materials in the field of flexible devices. The problem of insufficient has achieved widespread application in flexible electronics and other fields.

CN116959774BActive Publication Date: 2025-01-07SHENZHEN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210397350.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-15
Publication Date
2025-01-07
Estimated Expiration
2042-04-15

AI Technical Summary

Technical Problem

The application of MXenes materials in the field of flexible devices is limited by their poor mechanical strength and lack of elasticity, and the single MXenes aerogel material is insufficient in conductivity.

Method used

By combining carbon nanotubes with polyacrylonitrile fibers, electrospinning to form a composite fiber membrane, and freeze-thaw cross-linking and preoxidation carbonization with MXenes materials, a highly conductive and compressible MXenes matrix composite was prepared. Conductive aerogel.

Benefits of technology

It realizes the high conductivity, elasticity and ultralight properties of MXenes-based composite conductive aerogel. It is suitable for flexible electronics, energy and sensing fields. It has simple process, low cost and is easy to produce in industrialized production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116959774B_ABST
    Figure CN116959774B_ABST
Patent Text Reader

Abstract

The present application provides a MXenes-based composite conductive aerogel and a preparation method and application thereof, wherein the MXenes-based composite conductive aerogel comprises MXenes materials, carbon fibers, and carbon nanotubes, wherein the carbon fibers wrap the carbon nanotubes to form composite fibers, and the MXenes-based composite conductive aerogel has a three-dimensional interconnected porous network formed by the interpenetration of the composite fibers and the MXenes materials. The above-mentioned MXenes-based composite conductive aerogel has good conductivity, compressibility and light specific gravity, and has broad application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of preparation of conductive composite materials, and specifically relates to a MXenes-based composite conductive aerogel and a preparation method and application thereof. Background Art

[0002] Mxenes (i.e., two-dimensional transition metal carbides, nitrides or carbonitrides) are a new type of graphene-like layered two-dimensional material. It has broad application prospects in biomedicine, energy storage, catalysis and flexible electronics due to its high electrical conductivity, good hydrophilicity, excellent photothermal conversion properties and other characteristics.

[0003] In order to enrich the product forms of MXenes, two-dimensional MXenes can be transformed into three-dimensional aerogel materials by freeze-drying, but the interaction (hydrogen bond) between MXenes is weak, and the mechanical strength of a single MXenes aerogel material is poor and it does not have any elasticity, which limits its application in the field of flexible devices. Therefore, it is necessary to provide a conductive aerogel material based on MXenes. Summary of the invention

[0004] In view of this, the present application provides a MXenes-based composite conductive aerogel having high conductivity, high elasticity and ultra-light properties, and a preparation method and application thereof.

[0005] In a first aspect, the present application provides a method for preparing a MXenes-based composite conductive aerogel, comprising the following steps:

[0006] (1) mixing carbon nanotubes with ionic liquids and grinding to obtain carbon nanotubes modified with ionic liquids;

[0007] (2) dispersing the carbon nanotubes modified with the ionic liquid and polyacrylonitrile in a first solvent to obtain a spinning solution; and electrospinning the spinning solution to obtain a composite fiber membrane;

[0008] Cutting the composite fiber membrane into pieces and placing them in a second solvent to obtain a colloidal solution of composite nanofibers containing carbon nanotubes modified with ionic liquid and polyacrylonitrile fibers;

[0009] (3) mixing the colloidal solution with a MXenes material, subjecting the resulting mixed solution to a freeze-thaw cycle to physical crosslinking, thereby obtaining a composite hydrogel; and freeze-drying the composite hydrogel to obtain a composite aerogel;

[0010] (4) The composite aerogel is subjected to a pre-oxidation treatment at 200-300° C. in an oxygen-containing atmosphere, and then subjected to a carbonization treatment at 700-1000° C. in an inert atmosphere to obtain a MXenes-based composite conductive aerogel.

[0011] In step (1), the carbon nanotubes are mixed with the ionic liquid and then ground, so that the surface of the carbon nanotubes can be modified with the ionic liquid. More precisely, the surface of the carbon nanotubes can be coated with the ionic liquid, which can improve the stability and dispersibility of the carbon nanotubes and help the carbon nanotubes to fully exert their high conductivity in the final product.

[0012] In the embodiment of the present application, the type of the ionic liquid is not limited, and the cations constituting the ionic liquid may contain N elements, S elements, or P elements, etc. In some embodiments, the cations of the ionic liquid may be N-containing cations such as imidazole cations, pyridinium cations, piperidinium cations, and pyrrole cations. For example, the ion may be 1-methyl-3-butylimidazolium hexafluorophosphate, 1-methyl-3-butylimidazolium tetrafluoroborate, etc.

[0013] Optionally, the mass ratio of the carbon nanotubes to the ionic liquid is 100:(1-10). This mass ratio can ensure that an ionic liquid layer of suitable thickness is formed on the surface of the carbon nanotubes, so as to ensure that the dispersion and stability of the carbon nanotubes are good, while the proportion of carbon nanotubes in the overall material is not too low and the conductivity is better. In some embodiments, the mass ratio is 100:(2-8), for example, it can be 100:3, 100:5, 100:7, etc. Optionally, the grinding time can be 30 to 60 minutes; specifically, it can be 40min, 45min, 50min, etc. Further, before grinding the carbon nanotubes and the ionic liquid, the carbon nanotubes and the ionic liquid can be vacuum dried separately to remove moisture. Among them, the drying treatment can be a vacuum drying treatment at 100-110°C for 24 to 48h.

[0014] In the embodiment of the present application, in the spinning solution in step (2), the mass ratio of the polyacrylonitrile to the carbon nanotubes modified by the ionic liquid is 100:(1-5). The mass ratio of the polyacrylonitrile to the first solvent is 100:(5-15). In this way, the spinning solution can be guaranteed to have a suitable viscosity, thereby improving the preparation efficiency of the composite fiber membrane obtained by spinning; in addition, the mass ratio of polyacrylonitrile to the carbon nanotubes modified by the ionic liquid can also regulate the mass proportion of carbon fiber and carbon nanotubes in the final product to regulate its conductivity, toughness, etc. In some embodiments, the mass ratio of the polyacrylonitrile to the carbon nanotubes modified by the ionic liquid is 100:(1-3), for example, 100:2; the mass ratio of the polyacrylonitrile to the first solvent is 100:(5-10), for example, 100:6 or 100:8, etc.

[0015] Among them, the first solvent in the spinning solution is usually an organic solvent that can dissolve polyacrylonitrile, including but not limited to one or more of N,N-dimethylformamide (DMF), N-methylpyrrolidone (NMP), dimethyl sulfoxide (DMSO), tetrahydrofuran (THF), etc.

[0016] In some embodiments of the present application, the electrospinning can be carried out under the following conditions: the spinning voltage is 5 to 10 kV, the rotation speed of the fiber receiving device is 200 to 1000 rpm, the spinning distance is 5 to 10 cm, and the spinning time is 20 to 60 minutes. Among them, the fiber receiving device can be a roller for carrying the composite fiber membrane formed by the spinning solution; the spinning distance refers to the distance between the spinning needle for outputting the spinning solution and the fiber receiving device. Furthermore, the composite fiber membrane obtained by spinning in step (2) can also be dried to remove the second solvent therein. Among them, the drying treatment can be performed at 100 to 120°C for 24 to 48 hours in a vacuum drying process.

[0017] In step (2), after the spinning solution containing polyacrylonitrile and carbon nanotubes modified by ionic liquid is subjected to electrostatic spinning, the resulting composite fiber membrane includes a spinning membrane matrix formed by polyacrylonitrile fibers and carbon nanotubes modified by ionic liquids encapsulated therein. After being shredded and sheared, the composite fiber membrane will dissociate into composite nanofibers that are easy to fully disperse in a solvent, wherein the composite nanofibers include carbon nanotubes modified by ionic liquids and polyacrylonitrile fibers, and the polyacrylonitrile fibers encapsulate the carbon nanotubes modified by ionic liquids.

[0018] Optionally, the diameter of the composite nanofiber is 50-100 nm, and the length can be 1-10 μm. Optionally, the shearing speed can be 10000-30000 rpm; the shearing time can be 5-60 min. A higher shearing speed is conducive to fully dissociating the entire composite fiber membrane into individual composite fibers. The shearing time can be adjusted according to the size of the composite fiber membrane.

[0019] Optionally, the second solvent comprises a mixture of water and an alcohol solvent. Among them, the alcohol solvent comprises tert-butyl alcohol, or a mixture of tert-butyl alcohol and other alcohols (isobutyl alcohol, isopropyl alcohol, ethylene glycol, ethanol, etc.). Optionally, the mass ratio of water to the alcohol solvent can be 100:20. The above-mentioned composite fiber has good dispersibility in the second solvent containing water. Optionally, the concentration of the composite nanofiber in the colloidal solution is 2 to 10 mg / mL.

[0020] In step (3), the mass ratio of the composite nanofibers in the colloidal solution to the MXenes material is (5-100):100, preferably (10-90):100, and more preferably (20-80):100, such as 40:100, 50:100, 60:100, 70:100, etc. Among them, controlling the mass ratio of the composite nanofibers containing ionic liquid-modified carbon nanotubes and polyacrylonitrile fibers to the MXenes material within the above range is conducive to the final product being able to better balance good conductivity and mechanical properties.

[0021] In step (3), when preparing a mixed solution for forming a composite hydrogel, the MXenes material is added in any form and can be added in a solid form or in the form of a solution containing it. In some embodiments of the present application, the mixed solution is obtained by mixing the colloidal solution obtained in step (2) with an aqueous solution of the MXenes material. Among them, the mixing can specifically be stirred at a rotation speed of 10000 to 30000 rpm for 1 to 5 minutes. Optionally, the concentration of the aqueous solution of the MXenes material is 4 to 10 mg / mL.

[0022] In this application, the chemical formula of MXenes is M n+1 X n T x , wherein M is a transition metal element, X is a carbon element and / or a nitrogen element, n is an integer of 1-3, T x represents the surface group, T can be selected from O 2- OH - 、F - and NH4 + Further, the MXenes material may be specifically Ti3C2T x 、Ti2CT x 、(Ti 0.5 , Nb 0.5 )2CT x ,(V 0.5 ,Cr 0.5 )3C2T x 、Ta4C3T x 、V2CT x 、Nb2CT x 、Nb4C3T x 、(Nb 0.8 , Ti 0.2 )4C3T x 、(Nb 0.8 , Zr 0.2 )4C3T x 、Ti3CNT x 、Mo2TiC2T x、Mo2Ti2C3T x and Cr2TiC2T x One or more of. The above-mentioned MXenes are two-dimensional layered materials with a thickness of nanometers, which can be called "MXenes nanosheets". Among them, the number of layers of the MXenes material is 1-20 layers. More preferably, it is 2-10 layers. Preferably, the thickness of the MXenes material is 6-10nm. Optionally, the lateral size of the MXenes material can be 60-200nm. The lateral size refers to the length or width of the two-dimensional layered material.

[0023] In the present application, the preparation method of the MXenes material used in step (3) is not limited, and it can be obtained by acid etching, high temperature etching or vapor phase etching of the A element (such as Al element) in the precursor material MAX (M represents a transition metal element, A is usually Al or Si, and X includes C, N or C and N elements). Taking MAX as Ti3AlC2 as an example, a preparation method of MXenes is illustrated, which specifically includes the following steps:

[0024] 1) Ti3AlC2 powder is slowly added to a pre-prepared mixed solution of lithium fluoride (NaF) and concentrated hydrochloric acid (HCl), and an etching reaction is carried out at a temperature of 25 to 50°C for 16 to 48 hours; after the reaction is completed, the obtained reaction solution is centrifuged and washed, and the solid precipitate is collected until the centrifuged solution is neutral or nearly neutral;

[0025] 2) The solid precipitate is mixed with an intercalation agent (such as ethanol), and ultrasonically exfoliated in deionized water, and an aqueous solution containing MXenes material is obtained by centrifugation.

[0026] In step (3), the mixed solution formed by the colloidal solution and the MXenes material can be physically cross-linked after freeze-thaw cycle treatment to form a composite hydrogel containing MXenes material and composite nanofibers, wherein the MXenes material and the composite nanofibers interpenetrate each other, so that the composite hydrogel has a three-dimensional gel network structure, and the ionic liquid-modified carbon nanotubes are wrapped by polyacrylonitrile fibers and loaded in the three-dimensional gel network structure. The larger bulk viscosity of the composite hydrogel and the coating of its gel network help to further reduce the agglomeration of the MXenes material dispersed therein.

[0027] In step (3), the freeze-thaw cycle treatment process includes: first placing the mixed solution formed by the colloidal solution and the MXenes material on a hard substrate pre-frozen by liquid nitrogen (e.g., at a temperature of -80°C), then placing it in a freezer at -5 to -20°C for freezing; then thawing it at room temperature; and cycling the above freezing and thawing process multiple times. Placing the precursor solution that forms the composite hydrogel on a hard substrate pre-frozen by liquid nitrogen before freezing can guide the precursor solution to undergo "oriented freezing" so as to achieve oriented "physical cross-linking" in a freezing device with a higher temperature than the hard substrate, which is beneficial to improving the mechanical properties of the resulting composite hydrogel and ensuring the continuity and orderliness of the gel network structure.

[0028] Optionally, the number of cycles of the freeze-thaw process is 3 to 10 times, preferably 5 to 8 times, for example 6 or 7 times. Optionally, the total duration of the freezing process and the total duration of the thawing process are respectively in the range of 5 to 24 hours, preferably in the range of 12 to 20 hours, for example 14 hours, 18 hours, etc. Among them, the above-mentioned hard substrate can be a metal plate such as a copper plate, or other low-temperature resistant materials. The freezer can be a refrigerator, a freezer, etc. with a freezing function.

[0029] Optionally, after obtaining the composite hydrogel containing MXenes material and composite nanofibers, it can be placed in deionized water for dialysis treatment and then freeze-dried. The main purpose of the dialysis treatment is to remove the second solvent and purify the hydrogel. Optionally, the dialysis can be carried out at a temperature of 4-10°C, and the dialysis time can be 48-72h. Among them, the temperature for freeze-drying the composite hydrogel can be -20 to -80°C, for example, -20 to -40°C; the freeze-drying time can be 24 to 96h, for example, 48 to 96h, and further can be 48 to 72h.

[0030] Optionally, in step (4), the pre-oxidation treatment time is 30 to 120 minutes; the heating rate of the pre-oxidation treatment (specifically, the rate of heating from room temperature to the pre-oxidation temperature (200 to 300° C.)) is 1 to 5° C. / min. Pre-oxidation can improve the conductivity of the final product. The oxygen-containing atmosphere can be air or oxygen, and air is preferred because it is cheaper.

[0031] Optionally, the carbonization treatment time is 1 to 5 hours; the heating rate of the carbonization treatment (the rate of heating from room temperature to the temperature of the carbonization treatment) is 1 to 5°C / min. Preferably, the temperature of the carbonization treatment is 800 to 900°C. The carbonization treatment is mainly to carbonize the polypropylene fibers in the composite aerogel to form highly conductive carbon fibers to obtain a conductive composite material with good conductivity. Among them, the ionic liquid located on the surface of the carbon nanotubes is generally calcined and removed during the carbonization treatment. Optionally, the inert atmosphere includes one or more of argon (Ar) and helium (He).

[0032] In the preparation method of the above-mentioned MXenes-based composite conductive aerogel provided in this application, the carbon nanotubes modified with ionic liquids are electrospun together with polypropylene, and the formed spinning membrane is dissociated into a single composite nanofiber, and the composite nanofiber is cross-linked with the MXenes material to form an aerogel material, and after pre-oxidation and carbonization, an ultra-light, highly conductive, and compressible MXenes / carbon fiber / carbon nanotube composite conductive aerogel is obtained, which is expected to be applied to flexible wearable electronics, energy, sensing, environment and other fields. The above-mentioned preparation method has a simple process, is easy to operate, has low cost, high yield, and is easy to realize industrial production.

[0033] Optionally, the surface of the carbon fiber has a porous structure, which can be formed during the carbonization process of the above-mentioned preparation method.

[0034] An embodiment of the present application also provides a MXenes-based composite conductive aerogel, comprising a MXenes material, carbon fibers, and carbon nanotubes, wherein the carbon fibers wrap the carbon nanotubes to form composite fibers, and the MXenes-based composite conductive aerogel has a three-dimensional interconnected porous network formed by the interpenetration of the composite fibers and the MXenes material.

[0035] In the present application, the outer surface of the carbon nanotube is coated with carbon fiber, and the two constitute a core-shell structure. The carbon nanotube with outstanding conductivity can further improve the conductivity of the carbon fiber, and the outer carbon fiber is also conducive to contact and entanglement with the MXenes material. The above-mentioned three-dimensional interconnected porous network is formed by interconnecting and entanglement with the MXenes material through composite fibers. The conductivity of the carbon fiber located outside the composite fiber is higher than that of the MXenes material. It is in contact and connection with the MXenes material, which is conducive to reducing the contact resistance between the MXenes. In addition, the density of carbon fiber and carbon nanotube is low, and the toughness is higher than that of MXenes, especially the toughness of carbon nanotube is better. Their presence can make the specific gravity of the composite conductive aerogel small, and give it a certain toughness, so that it has a certain compressibility, which is conducive to its application in flexible devices. Therefore, the above-mentioned MXenes-based composite conductive aerogel has good conductivity, compressibility and lighter specific gravity.

[0036] In the embodiment of the present application, at least a portion of the MXenes material is wrapped with the carbon fiber. The carbon fiber not only plays a mechanical reinforcement role, but also reduces the contact resistance between the two-dimensional layered material MXenes and the contact resistance between the MXenes sheets due to its high conductivity.

[0037] Optionally, in the MXenes-based composite conductive aerogel, the mass proportion of the MXenes material is 50%-95.24%, the mass proportion of the carbon nanotubes is 0.047%-2.38%; and the mass proportion of the carbon fiber is 4.53%-49.5%.

[0038] The MXenes-based composite conductive aerogel provided in the present application enriches the product form of MXenes, and has good conductivity, compressibility and light specific gravity as described above, and is expected to be used in the fields of energy (solar cells, lithium-ion batteries, aluminum-ion batteries, etc.), photovoltaics, photothermals, electromagnetic shielding, sensing, etc.

[0039] The embodiments of the present application also provide applications of the above-mentioned MXenes-based composite conductive aerogel in batteries, optoelectronic devices, photothermal devices, sensors, and electromagnetic shielding components.

[0040] Among them, the battery includes electrochemical batteries (such as lithium ion batteries, aluminum ion batteries, sodium secondary batteries, potassium secondary batteries, magnesium secondary batteries, zinc secondary batteries, etc.), solar cells, etc.

[0041] Furthermore, MXenes-based composite conductive aerogels can be used as electrodes or conductive agents in batteries, optoelectronic devices, photothermal devices, sensors, etc. In particular, the above batteries, optoelectronic devices, photothermal devices, sensors, etc. can be flexible, and they can be used in flexible wearable devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 This is a macroscopic photograph of the MXenes-based composite conductive aerogel prepared in Example 1 of the present application.

[0043] Figure 2 This is a macroscopic photograph of the pure MXenes aerogel material prepared in Comparative Example 1.

[0044] Figure 3 This is a macroscopic photograph of the MXenes / carbon fiber composite aerogel material prepared in Comparative Example 2. DETAILED DESCRIPTION

[0045] Described below are exemplary implementations of the embodiments of the present application. It should be noted that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the embodiments of the present application. These improvements and modifications are also considered to be within the scope of protection of the embodiments of the present application.

[0046] The following is a further description of the embodiments of the present application in multiple embodiments. Unless otherwise specified, the raw materials and other chemical reagents used in the embodiments of the present application are all commercially available products.

[0047] Example 1

[0048] A method for preparing a MXenes-based composite conductive aerogel comprises the following steps:

[0049] (1) Preparation of ionic liquid modified carbon nanotubes:

[0050] The ionic liquid (specifically 1-methyl-3-butylimidazole hexafluorophosphate) and carbon nanotubes were vacuum dried at 110° C. for 48 hours respectively; the dried carbon nanotubes and ionic liquid were placed in an agate mortar at a mass ratio of 100:5 and mechanically ground for 40 minutes to obtain an ionic liquid-modified carbon nanotube composite material for standby use.

[0051] (2) Preparing a colloidal solution of composite nanofibers containing ionic liquid-modified carbon nanotubes and polyacrylonitrile, specifically comprising the following steps:

[0052] 2-a): The polyacrylonitrile is vacuum dried at 110° C. for 48 h, and then dispersed in N,N-dimethylformamide (DMF) with the carbon nanotube composite material modified by the ionic liquid, wherein the mass ratio of polyacrylonitrile to DMF is 100:8, and the mass ratio of polyacrylonitrile to the carbon nanotube composite material modified by the ionic liquid is 100:2, and after continuous stirring, a uniform spinning solution is obtained;

[0053] 2-b): The spinning solution is subjected to electrostatic spinning to obtain a composite fiber membrane of polyacrylonitrile / carbon nanotubes / ionic liquid, wherein the electrostatic spinning is carried out under the following conditions: the spinning voltage is 10 kV, the fiber receiving device is a roller, the rotation speed is 500 rpm, the spinning distance is 10 cm, and the spinning time is 60 minutes. Afterwards, the composite fiber membrane is vacuum dried at 110° C. for 48 hours and set aside.

[0054] 2-c): The composite fiber membrane is cut into pieces and added into a mixed solvent prepared by deionized water and tert-butanol in a mass ratio of 100:20, and high-speed shearing is performed at a speed of 20,000 rpm for 30 minutes to obtain a colloidal solution of carbon nanotube / polyacrylonitrile composite nanofibers modified with ionic liquid, which is set aside; wherein the concentration of the composite nanofibers is 5 mg / mL.

[0055] (3) Preparing a composite aerogel of composite nanofibers / MXenes, specifically comprising:

[0056] 3-a): Preparation of MXenes material: Ti3AlC2 powder was slowly added to a pre-prepared mixed solution of lithium fluoride (LiF) and concentrated hydrochloric acid (HCl), and the etching reaction was carried out at a temperature of 30°C for 24 hours. The obtained reaction solution was centrifuged and washed, and the solid precipitate was collected until the centrifuge solution was neutral or nearly neutral; the solid was then mixed with the intercalation agent-ethanol, and then ultrasonically exfoliated in deionized water, and the MXenes material (specifically Ti3C2T x The concentration of the aqueous solution of nanosheets is about 5 mg / mL.

[0057] 3-b): The aqueous solution of MXenes is mixed with the colloidal solution of the composite nanofibers in step (2), and stirred at a speed of 20,000 rpm for 3 minutes to obtain a uniform mixed solution; wherein the mass ratio of the MXenes material to the composite nanofibers is 100:60.

[0058] 3-c): The mixed solution obtained in 3-b) above is placed on a copper plate pre-frozen with liquid nitrogen for "oriented freezing", and then placed in a freezer for freezing to slowly "physically crosslink"; then slowly thawed at room temperature; the above freezing and thawing process is repeated 7 times to obtain a physically crosslinked MXenes / composite nanofiber composite hydrogel; wherein the total freezing and thawing time is 14 hours, respectively.

[0059] 3-d): The physically cross-linked composite hydrogel was dialyzed in deionized water and then freeze-dried at -40°C for 72 hours to obtain a MXenes / composite nanofiber composite aerogel.

[0060] (4) Heat treatment of composite aerogel

[0061] The composite aerogel obtained in step (3) is subjected to a pre-oxidation treatment in air, wherein the pre-oxidation temperature is 280° C., the heating rate from room temperature to the pre-oxidation temperature is 4° C. / min, and the pre-oxidation time is 60 min;

[0062] The pre-oxidized composite aerogel was carbonized in an Ar atmosphere, wherein the carbonization temperature was 1000°C, the heating rate from room temperature to the carbonization temperature was 5°C / min, and the carbonization time was 3h, and finally a MXenes-based composite conductive aerogel containing MXenes, carbon fibers and carbon nanotubes was obtained.

[0063] In the MXenes-based composite conductive aerogel provided in Example 1, the mass proportion of MXenes material is about 62.5%, the mass proportion of carbon nanotubes is about 0.74%, and the mass proportion of carbon fiber is about 36.76%.

[0064] In order to highlight the beneficial effects of the present application, the following comparative examples are provided.

[0065] Comparative Example 1

[0066] A pure MXenes aerogel, the preparation process of which is different from that of Example 1 in that no polyacrylonitrile fibers and carbon nanotubes are added. That is, the MXenes solution is directly subjected to a freeze-thaw cycle, then freeze-dried, and then carbonized under an Ar atmosphere to obtain a pure MXenes aerogel, that is, the mass proportion of the MXenes material is 100%.

[0067] Comparative Example 2

[0068] A MXenes / carbon fiber composite aerogel, the preparation process of which is different from that of Example 1 in that: the MXenes material is mixed with only polyacrylonitrile fibers dissociated from a spun fiber membrane of polyacrylonitrile, and does not contain carbon nanotubes modified with ionic liquids.

[0069] In the MXenes / carbon fiber composite aerogel material prepared in Comparative Example 2, the mass proportion of MXenes material is approximately 62.5%, the mass proportion of carbon nanotubes is approximately 0, and the mass proportion of carbon fiber is approximately 37.5%.

[0070] Figure 1 This is a macroscopic photograph of the MXenes-based composite conductive aerogel prepared in Example 1 of the present application. Figure 1 It can be seen that the composite conductive aerogel has a regular shape, no obvious cracks on the surface, and its volume shrinkage in the reaction container is small, which not only ensures the smaller density of the conductive aerogel, but also maintains its rich internal pore structure. Figure 2 This is a photo of pure MXenes aerogel material (Comparative Example 1). It can be seen that the pure MXenes aerogel material has more surface grooves and cracks, and the sample is more brittle. This may be due to the weak interaction between MXenes flakes and the loose stacking of flakes. Figure 3 This is a macroscopic photograph of the MXenes / carbon fiber composite aerogel material prepared in Comparative Example 2. Figure 3 It can be seen that compared with pure MXenes aerogel materials, the introduction of carbon fibers can improve the compactness of MXenes materials, and the samples show improved regularity. Figure 1 Slightly worse.

[0071] Further, the conductivity and mechanical recovery properties of each conductive aerogel material of Example 1 and Comparative Examples 1-2 were tested, and the results are shown in Table 1. The test conditions for mechanical properties are as follows: Instrument: Instron 9566, pressure sensor: 500N; test fixture: compression fixture; test conditions: room temperature; compression speed: 1mm / min; detection mode: compression recovery mode. The test of conductivity was tested using Mitsubishi Chemical low resistance instrument (four-probe method).

[0072] Table 1

[0073] Sample No. First response rate (%) Third response rate (%) Sixth response rate (%) Resistivity (mΩ·cm) Example 1 89.5 89.0 88.5 26.5 Comparative Example 1 0 0 0 15.5 Comparative Example 2 85.5 80.5 78.3 27.6

[0074] It can be seen from Table 1 that the pure MXenes aerogel material of Comparative Example 1 does not have mechanical recovery, while after the introduction of polyacrylonitrile fiber in the preparation process of Comparative Example 2 (wherein the mass ratio of MXenes material to polyacrylonitrile fiber is 100:60), the obtained composite aerogel product can be given a certain recovery, but its conductivity is significantly reduced.

[0075] In summary, the composite conductive aerogel provided in Example 1 of the present application has a regular shape and high recoverability. After six reciprocating stretching, the recovery rate of the composite aerogel is still higher than 95%. At the same time, its conductivity is also relatively good, and it has great potential for use in the field of flexible electronic devices.

[0076] Example 2

[0077] The difference between Example 2 and Example 1 is that in step (2), the mass ratio of polyacrylonitrile to the carbon nanotube composite material modified with ionic liquid is 100:1.

[0078] In the MXenes-based composite conductive aerogel prepared in Example 2, the mass proportion of MXenes material is about 62.5%, the mass proportion of carbon nanotubes is about 0.37%, and the mass proportion of carbon fiber is about 37.13%.

[0079] Example 3

[0080] The difference between Example 3 and Example 1 is that in step (2), the mass ratio of polyacrylonitrile to the carbon nanotube composite material modified with ionic liquid is 100:3.

[0081] In the MXenes-based composite conductive aerogel prepared in Example 3, the mass proportion of MXenes material is about 62.5%, the mass proportion of carbon nanotubes is about 1.09%, and the mass proportion of carbon fiber is about 36.41%.

[0082] Example 4

[0083] The difference between Example 4 and Example 1 is that in step (2), the mass ratio of polyacrylonitrile to the carbon nanotube composite material modified with ionic liquid is 100:5.

[0084] In the MXenes-based composite conductive aerogel prepared in Example 4, the mass proportion of MXenes material is approximately 62.5%, the mass proportion of carbon nanotubes is approximately 1.79%, and the mass proportion of carbon fiber is approximately 35.71%.

[0085] Example 5

[0086] The difference between Example 5 and Example 1 is that in step (3), the mass ratio of the MXenes material to the composite nanofibers in the colloidal solution is 100:90.

[0087] In the MXenes-based composite conductive aerogel prepared in Example 5, the mass proportion of MXenes material is approximately 52.63%, the mass proportion of carbon nanotubes is approximately 0.93%, and the mass proportion of carbon fiber is approximately 46.44%.

[0088] Example 6

[0089] The difference between Example 6 and Example 1 is that in step (3), the mass ratio of the MXenes material to the composite nanofibers in the colloidal solution is 100:100.

[0090] In the MXenes-based composite conductive aerogel prepared in Example 6, the mass proportion of MXenes material is about 50%, the mass proportion of carbon nanotubes is about 0.98%, and the mass proportion of carbon fiber is about 49.02%.

[0091] The MXenes-based composite conductive aerogels provided in Examples 2-6 of the present application also have excellent mechanical recovery properties and good conductivity. The relevant test results are summarized in Table 2 below.

[0092] Table 2

[0093] Sample No. First response rate (%) Sixth response rate (%) Resistivity (mΩ·cm) Example 2 85.0 84.5 28.0 Example 3 86.0 85.5 26.0 Example 4 90.5 90.0 25.5 Example 5 86.0 85.8 35.5 Example 6 91.5 91.0 40.8

[0094] It can be seen from Table 2 that when the mass proportions of MXenes materials, carbon nanotubes, and carbon fibers in the composite conductive aerogels of Examples 2-6 are different from those in Example 1, the mechanical recovery properties and conductivity of each composite conductive aerogel are also different to a certain extent, but the recovery of the composite conductive aerogel in each example is higher than that of pure MXenes aerogel, and the conductivity is better than that of their respective corresponding comparative examples (MXenes / carbon fiber composite aerogels without adding carbon nanotubes under the same conditions).

[0095] The above-mentioned embodiments only express several exemplary implementations of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that, for those of ordinary skill in the art, several modifications and improvements can be made without departing from the concept of the present application, and these modifications and improvements all belong to the protection scope of the present application.

Claims

1. A method for preparing a MXenes-based composite conductive aerogel, characterized in that: The following steps are involved: (1) mixing carbon nanotubes with ionic liquids and grinding to obtain carbon nanotubes modified with ionic liquids; (2) dispersing the carbon nanotubes modified with the ionic liquid and polyacrylonitrile in a first solvent at a mass ratio of (1-5):100 to obtain a spinning solution; Electrospinning the spinning solution to obtain a composite fiber membrane; Cutting the composite fiber membrane into pieces and placing them in a second solvent to obtain a colloidal solution of composite nanofibers containing carbon nanotubes modified with ionic liquid and polyacrylonitrile fibers; (3) mixing the colloidal solution with the MXenes material at a mass ratio of the composite nanofibers to the MXenes material of (5-100):100, subjecting the obtained mixed solution to a freeze-thaw cycle treatment to generate physical crosslinking to obtain a composite hydrogel; and freeze-drying the composite hydrogel to obtain a composite aerogel; (4) The composite aerogel is subjected to a pre-oxidation treatment at 200-300° C. in an oxygen-containing atmosphere, and then subjected to a carbonization treatment at 700-1000° C. in an inert atmosphere to obtain a MXenes-based composite conductive aerogel.

2. The preparation method according to claim 1, characterized in that In step (1), the mass ratio of the carbon nanotubes to the ionic liquid is 100:(1-10).

3. The preparation method according to any one of claims 1 to 2, characterized in that: In step (2), the shearing rotation speed is 10000 to 30000 rpm.

4. The preparation method according to claim 1, characterized in that: In step (3), the freeze-thaw cycle treatment includes: first placing the mixed solution of the colloidal solution and the MXenes material on a hard substrate pre-frozen by liquid nitrogen, and then freezing it in a freezer at -10 to -20°C; then thawing it at room temperature; and repeating the above freezing and thawing process multiple times.

5. The preparation method according to claim 1, characterized in that: In step (4), the oxygen-containing atmosphere is air, the heating rate of the pre-oxidation treatment is 1 to 5°C / min, and the time of the pre-oxidation treatment is 30 to 120 min; The heating rate of the carbonization treatment is 1 to 5°C / min, and the time of the carbonization treatment is 1 to 5 hours.

6. A MXenes-based composite conductive aerogel, characterized in that: The MXenes-based composite conductive aerogel is prepared by the preparation method according to any one of claims 1 to 5, comprising MXenes material, carbon fiber, and carbon nanotubes, wherein the carbon fiber wraps the carbon nanotube to form a composite fiber, and the MXenes-based composite conductive aerogel has a three-dimensional interconnected porous network formed by the interpenetration of the composite fiber and the MXenes material.

7. The MXenes-based composite conductive aerogel according to claim 6, characterized in that In the MXenes-based conductive composite material, the mass proportion of the MXenes material is 50%-95.24%, the mass proportion of the carbon nanotubes is 0.047%-2.38%; and the mass proportion of the carbon fiber is 4.53%-49.5%.

8. Application of the MXenes-based composite conductive aerogel as described in any one of claims 6 to 7 or the MXenes-based composite conductive aerogel prepared by the preparation method as described in any one of claims 1 to 5 in batteries, optoelectronic devices, photothermal devices, sensors, and electromagnetic shielding.

Citation Information

Patent Citations

  • 3D super-elastic electrospun carbon nanofiber / MXene composite aerogel and collaborative assembly preparation method thereof

    CN113233466A

  • Preparation method of MXene-CNT / carbon aerogel composite material

    CN113645820A